Perhatian Orang Tua dan Penguasaan Materi Prasyarat Terhadap Belajar Matematika - Widiyanto Widiyanto (Jurnal Ilmu Pendidikan Indonesia, 2019)
This study aims to study parental attention (X1), mastery of material as a requirement (X2) and jointly with parental attention (X1) and mastery of material related to the suitability of learning outcomes of students of SMAN 4 Kota Sorong (Y). This type of research is quantitative in the form of correlational research. Purposive sampling is a sampling technique used in this study. The results showed that parents' attention and mastery of material had a significant relationship to mathematics learning achievement of Sorong City 4 High School students, namely 63.8% and 47.6%. Together, parental attention and mastery of prerequisite material have a significant influence on mathematics learning achievement of SMAN 4 Sorong City students, amounting to 70.6%.